THE EFFECT OF THE FIVE FINGER RETELLING TECHNIQUE ON STUDENTS' SPEAKING SKILL - Sutedja, Iis Rismawati (2014)
This study is aimed to know the effect of the five fingers retelling technique in improving the students' speaking skill. This study was designed by using a quasi-experimental. There were two groups, experimental and control group without random selection. Both groups were from the same population. This study was conducted at the eighth grade of a junior high school. The data were obtained from tests and questionnaires. The results of data analysis showed that the five fingers retelling technique succeeded in developing the students' speaking skill because there was a significant difference between the post-test scores of students in experimental group and control group. The five finger retelling technique was very effective to improve the students' speaking skill. Overall the students' perceptions toward the implementation of five fingers retelling technique were positive because they enjoyed the learning process and they were interested in the story retelling. Finally, with reference to the finding, it indicates that the five finger retelling technique is recommended to be implemented by the English teachers in their teaching activity.